The incorporation of Feng Shui philosophy towards the shape of logo design of Hong Leong Bank Berhad / Foong Hock Kuen - Foong, Hock Kuen (2017)
This research discovers the underlying caused in designing the shapes of logo design based on Feng Shui philosophy. Through this discovery, the researcher selected Hong Leong Bank Berhad as an organization sample for the subject matters of research due to its logo designed by Grand Master Feng Shui Lillian Too. The research covers the understanding of Feng Shui Philosophy theory and the Formalism theory as design principle. In addition, interviews conducted towards graphic designers as an expert sampling to discover the underlying causes of the Feng Shui philosophy and their perceptions about the incorporation of Feng Shui philosophy in designing the shapes of logo design. The research discovery able to justify and analyzed the feasibility and possibilities of incorporation of Feng Shui philosophy in designing the shape of logo design.